2022
DOI: 10.3847/1538-4357/ac3dfa
|View full text |Cite
|
Sign up to set email alerts
|

Now You See It, Now You Don’t: Star Formation Truncation Precedes the Loss of Molecular Gas by ∼100 Myr in Massive Poststarburst Galaxies at z ∼ 0.6

Abstract: We use ALMA observations of CO(2–1) in 13 massive (M * ≳ 1011 M ⊙) poststarburst galaxies at z ∼ 0.6 to constrain the molecular gas content in galaxies shortly after they quench their major star-forming episode. The poststarburst galaxies in this study are selected from the Sloan Digital Sky Survey spectroscopic samples (Data Release 14) based on their spectral shapes, as part of the Studying QUenching at Intermediate-z Galaxies: Gas, angu … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(61 citation statements)
references
References 111 publications
9
52
0
Order By: Relevance
“…Sample galaxies show no radial age gradients, implying quenching took place uniformly throughout the galaxies (Setton et al 2020). Previous ALMA observations of a sample of SQuIGG LE post-starbursts found that the quenching of star formation surprisingly does not require the total removal/destruction of the cold molecular gas reservoir, but this cold gas does rapidly disappear over the ensuing ∼100 Myr post-quenching (Suess et al 2017;Bezanson et al 2022).…”
Section: Introductionmentioning
confidence: 93%
“…Sample galaxies show no radial age gradients, implying quenching took place uniformly throughout the galaxies (Setton et al 2020). Previous ALMA observations of a sample of SQuIGG LE post-starbursts found that the quenching of star formation surprisingly does not require the total removal/destruction of the cold molecular gas reservoir, but this cold gas does rapidly disappear over the ensuing ∼100 Myr post-quenching (Suess et al 2017;Bezanson et al 2022).…”
Section: Introductionmentioning
confidence: 93%
“…However, in a previous study of CO(2-1) for a small (13 galaxies) subsample of  L SQuIGG E, we do not see evidence of centrally concentrated molecular gas or continuum emission in the detected galaxies at ∼1″ resolution. We measure molecular gas effective radii on the order of kiloparsecs and do not detect continuum emission in all but one galaxy (Bezanson et al 2022). As such, we assume dust obscuration informed by our best fits to IR spectrophotometric data.…”
Section: Testing the Central Starburst Scenariomentioning
confidence: 99%
“…Crucially, these spectra allow us to characterize the properties of the burst to measure the time since star formation was quenched and to track the evolution of the sample in key properties as a function of the time since quenching. This sample has allowed us to study in detail the link between the star formation shutdown and active galactic nucleus (AGN) incidence (Greene et al 2020), molecular gas content (Suess et al 2017;Bezanson et al 2022), and the incidence of mergers (M. Verrico et al 2022, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying how long galaxies have been quenched allows us to construct a timeline of how various galaxy properties evolve after star formation shuts down. Because it is impossible to watch a single galaxy evolve through the quenching process, cross-sectional studies using accurate post-quenching ages are the only way to gain an understanding of how galaxy structure, active galactic nuclei (AGN) activity, molecular gas contents, and other key properties change throughout the quenching process (e.g., French et al 2018;Bezanson et al 2022).…”
Section: Introductionmentioning
confidence: 99%